Tooth Morphogenesis and FGF4 Expression During Development of Molar Tooth in Three Muroid Rodents: Calomyscus elburzensis (Calomyscidae), Mesocricetus auratus (Cricetidae) and Mus musculus (Muridae). Issue 12 (9th September 2017) - Hamidi, Kordiyeh; Darvish, Jamshid; Matin, Maryam M.; Javanmard, Athar Sadat; Kilpatrick, C. William
ABSTRACT: To date, no studies have examined the tooth formation during developmental stages of brush‐tailed mice (Calomyscidae) and true hamsters (Cricetidae). Herein, we compared the timing of tooth morphogenesis and FGF4 expression pattern during development of the first lower molar in Goodwin's brush‐tailed mouse, Calomyscus elburzensis with two other muroid rodents; the house mouse, Mus musculus (Muridae), model organism for tooth morphogenesis, and the golden hamster, Mesocricetus auratus which shares great similarities in cusp pattern with brush‐tailed mice. All three species were bred in captivity and developing embryos were isolated at different embryonic days (E). Histological evaluation of lower molars was performed and spatiotemporal pattern of FGF4 expression was determined by immunohistochemistry. Results indicated that morphogenesis of the tooth cusps starts at the beginning of the cap stage of the first lower molar (E14 in house mouse, about E11.5 in golden hamster and E22 in Goodwin's brush‐tailed mouse). During the cap to bell stage (E15 in house mouse, E12 in golden hamster and at about E24 in Goodwin's brush‐tailed mouse), a decrease in the expression of FGF4 was observed in the mesenchyme, except for the cusp tips. According to our observations, the developmental process of the first lower molar formation in Goodwin's brush‐tailed mouse began much later as compared with the other two species. Despite the differences in the temporal pattern of molar development between these three members of the same superfamily (Muroidea), the correlation in the expression of FGF4 with specific stages of tooth morphogenesis supported its regulatory function. Anat Rec, 300:2138–2149, 2017. © 2017 Wiley Periodicals, Inc.